2004
DOI: 10.2172/15010483
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Tissue Concentrations of Chromium and Fish Condition in Juvenile Fall Chinook Salmon from the Hanford Reach of the Columbia River

Abstract: This study involved the collection of juvenile fall Chinook salmon and Columbia River water samples to assess whether fall Chinook salmon were exposed to chromium that upwells into the river from contaminated groundwater originating at the Hanford Site. Juvenile fall Chinook salmon were seined and water samples were collected from three locations in the Hanford Reach during the period of juvenile salmon freshwater residency in early May, mid-May, and mid-June 2002. The concentrations of chromium in fish and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The tangible outcome of the project, which required over 5 years to complete, was a report to DOE laying out our findings (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The main findings were that: (1) salmon life cycles are varied and complex (involving spring and fall runs, Healey, 1991), (2) having good population estimates by species and runs is critical (Hyun et al., 2012a,b), (3) several species of salmon spend a significant part of their life cycle in the Columbia River (and mainly in the Hanford Reach) where they spawn (Hayes et al., 2013), (4) contaminants are not viewed generally by the State or DOE as a significant stressor on salmon, especially compared to other stressors (CRESP, 2015; NRC, 1996; Regetz, 2003; Tiller et al., 2004), (5) laboratory experiments indicated that there is a great deal of variability in results, no effects were found at Hanford‐relevant chromium exposures on fertilization, hatching, and exposure of alevins (early stage on salmon), but there were some laboratory effects of chromium on later stages of fry (Farag et al., 2006a,b; Patton et al., 2007), and (6) at some periods of time the fry may be vulnerable to chromium if they remain near the gravel surface where the pore water and river water meet (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The Tribes, however, remained concerned about potential long‐term effects of contaminants on eggs and fry of salmon (especially the DNA, R. Jim, Nov. 2014).…”
Section: Hanford Site As a Case Study: Multiple Ecologicies Stakehold...mentioning
confidence: 99%
“…The tangible outcome of the project, which required over 5 years to complete, was a report to DOE laying out our findings (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The main findings were that: (1) salmon life cycles are varied and complex (involving spring and fall runs, Healey, 1991), (2) having good population estimates by species and runs is critical (Hyun et al., 2012a,b), (3) several species of salmon spend a significant part of their life cycle in the Columbia River (and mainly in the Hanford Reach) where they spawn (Hayes et al., 2013), (4) contaminants are not viewed generally by the State or DOE as a significant stressor on salmon, especially compared to other stressors (CRESP, 2015; NRC, 1996; Regetz, 2003; Tiller et al., 2004), (5) laboratory experiments indicated that there is a great deal of variability in results, no effects were found at Hanford‐relevant chromium exposures on fertilization, hatching, and exposure of alevins (early stage on salmon), but there were some laboratory effects of chromium on later stages of fry (Farag et al., 2006a,b; Patton et al., 2007), and (6) at some periods of time the fry may be vulnerable to chromium if they remain near the gravel surface where the pore water and river water meet (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The Tribes, however, remained concerned about potential long‐term effects of contaminants on eggs and fry of salmon (especially the DNA, R. Jim, Nov. 2014).…”
Section: Hanford Site As a Case Study: Multiple Ecologicies Stakehold...mentioning
confidence: 99%
“…Aquatic species show a wide range of Cr concentrations in their tissues. Ambedkar and Muniyan (2011) report Cr levels ranging from 0.70 to 1.28 ppm in the muscle of several freshwater species from contaminated areas and Tiller et al (2004) obtained Cr as high as 9.4 ppm in Oncorhynchus spp. The concentrations of Cr in ammocoetes ranged from 0.270 to 1.57 ppm and apparently do not seem to change with size (P= 0.500).…”
Section: X1mentioning
confidence: 99%